2019
DOI: 10.20473/jipk.v11i1.12458
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Kitosan Emerita sp. Sebagai Bahan Pengawet Alternatif pada Ikan Belanak (Mugil cephalus) <br><i>[Chitosan Emerita sp. as a Preservative Alternative in Mugil cephalus]<i>

Abstract: Kata Kunci:Kitosan, Emerita sp.,pengawet ikan Abstrak Emerita sp. dapat diolah kitosan sebagai alternatif bahan pengawet ikan. Tujuan penelitian ini adalah untuk mengetahui aktivitas kitosan Emerita sp. dalam menghambat pertumbuhan mikroorganisme pembusuk pada ikan sehingga dapat digunakan sebagai bahan pengawet alternatif. Sampel Emerita sp. diperoleh dari pesisir pantai Widarapayung,Cilacap. Karakteristik kitosan Emerita sp. dianalisa melalui uji FTIR dan uji proksimat. Aktivitas kitosan Emerita sp. sebagai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(4 reference statements)
1
1
0
3
Order By: Relevance
“…However, the differences of moisture content between the fish treated with different chitosan concentrations was not statistically significant which might be caused by the accumulation of moisture in the fish due to the formed film that trapped the moisture and oxygen inside the fish. This result was similar to the study conducted by Agustini (2007) and Wittriansyah et al (2019) where the use of 0.5% and 1.0% of chitosan did not significantly affect the moisture content of salted anchovies (Stolephorus heterolobus).…”
Section: Moisture Contentsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the differences of moisture content between the fish treated with different chitosan concentrations was not statistically significant which might be caused by the accumulation of moisture in the fish due to the formed film that trapped the moisture and oxygen inside the fish. This result was similar to the study conducted by Agustini (2007) and Wittriansyah et al (2019) where the use of 0.5% and 1.0% of chitosan did not significantly affect the moisture content of salted anchovies (Stolephorus heterolobus).…”
Section: Moisture Contentsupporting
confidence: 91%
“…Table 1 showed that although no mould was developed on the fish that was dried at 67°C, there was a growth of 17 x 101 CFU/gr of microbial colonies. This was because chitosan can inhibit the growth of these microorganisms by covering the entire surface of the fish through thin film layer which will inhibit the penetration of oxygen and water through the surface of the fish body, resulting in the inhibition of aerobic microbes development (Hui 2007;Sarwono 2010;Wittriansyah et al 2019).…”
Section: Total Plate Countmentioning
confidence: 99%
“…Undur-undur laut biasanya disebut yutuk. Yutuk merupakan salah satu bahan yang banyak dimanfaatkan sebagai umpan untuk memancing, pakan ternak dan mengolahnya menjadi makanan ringan seperti rempeyek (Wittriansyah et al, 2019). Yutuk (Emerita sp.)…”
Section: Pendahuluanunclassified
“…di Indonesia dapat ditemukan di pantai barat Sumatera, pantai selatan Jawa, dan pantai Sulawesi. Sebaran Yutuk di pantai selatan Jawa khususnya melibatkan wilayah Yogyakarta (Kabupaten Bantul dan Kulonprogo) serta daerah pesisir selatan mulai dari pantai Cilacap hingga pantai Kebumen (Wittriansyah et al, 2019).…”
Section: Pendahuluanunclassified
“…Sebagai perbandingan kadar air tepung tulang sidat terhadap tepung ikan lainnya adalah, tepung tulang ikan tuna 5.6% (Trilaksani et al, 2006), tepung tulang ikan patin sebesar 6.69% (Tababaka, 2004) dan tepung tulang ikan madidihang 3,76% (Maulida, 2005). Kadar air pada suatu bahan sangat dipengaruhi pada proses pengeringan (Wittriansyah et al, 2019). Proses pengeringan tepung tulang sidat sendiri dilakukan melalui proses oven.…”
Section: Hasil Uji Proksimatunclassified